Development and characterization of solid dispersion-based orodispersible tablets of cilnidipine - Murugesan Mohana; Sankaranarayanan Vijayalakshmi (Beni-Suef University Journal of Basic and Applied Sciences, 2022)
Abstract Background Cilnidipine, a calcium channel blocker, is the first-line drug for hypertension and belongs to Biopharmaceutics Classification System II. To mitigate its extensive first-pass metabolism and improve patient compliance, the present study was performed to develop and characterize solid dispersion-based orodispersible tablets. Results The phase solubility study with polyvinyl pyrrolidone 15% has shown a 140-fold increase in solubility. X-ray diffraction and differential scanning calorimetry studies emphasized the conversion of solid dispersion from crystalline to amorphous state. Solid dispersion 3 resulted in 142-fold improvement in solubility, 96% of drug content, and percentage drug release was 71.9% at 60 min. F11 containing crospovidone (10 mg) and sodium starch glycolate (16 mg) in combination at higher concentration as super-disintegrants showed the least disintegration time of 26.6 s. In vitro dissolution results are subjected to statistical analysis and found that the formulation (F11) has shown an increased dissolution rate (88.62% at 10 min), compared to the marketed formulation (83% at 60 min). Conclusions Solid dispersion prepared by a solvent evaporation method using PVP as a carrier can be utilized for enhancing the solubility of cilnidipine. The incorporation of super-disintegrants in combination improves the dissolution rate of orodispersible tablets. Further, the study can be substantiated by performing stability and in vivo studies in the future. Graphical Abstract